PEMERIKSAAN KESEHATAN GRATIS PADA LANSIA DESA PONGKA KECAMATAN TELLU SIATTINGE KAB. BONE TAHUN 2024 - Sumarni, Sumarni; Susilawati, Susilawati; Emawati, Emawati; Sriwidyastuti, Sriwidyastuti; Sulfiya Ninsi (Nusantara Hasana Journal, 2025)
Degenerative diseases are diseases that are often suffered by the elderly. Degenerative diseases are diseases caused by decreased organ function. Some degenerative diseases that are often suffered by the elderly are hypertension, coronary heart disease, diabetes mellitus, gout, etc. This community service aims to provide health services to the elderly in Pongka Village, Tellu Siattinge District, Bone Regency. The results of the community service activities show that health checks on the elderly in Pongka Village obtained blood pressure checks in the hypertension category for 21 elderly (77.8%), cholesterol level checks in the high category for 11 elderly (40.7%) and blood sugar level checks in the high category for 18 elderly (66.7%). Recommendations recommended in efforts to improve health for the elderly in Pongka Village include increasing public knowledge, especially the elderly, about factors related to the occurrence of a disease, especially hypertension, cholesterol levels and blood sugar levels through health education.